Role of Customer in Marketing and Development (RCMD) – a literature review - Oria, Ehsanullah; Perdhana, Mirwan Surya (Asian Management and Business Review, 2021)
The purpose of this article is to review empirical researches on role of customer in marketing and development (RCMD) and betterment of the firm’s performance and pave the way for future researches. This article is a cumulative literature review of empirical articles on (RCMD). In previous empirical studies two units of analysis has been conducted (individual and firm unit) which includes two viewpoints: The customers' viewpoint and the firms’ viewpoint. The customers’ viewpoint that consider RCMD issues from customer perspectives and stresses on practices of customers in marketing and development. The company's viewpoint looks at RCMD issues from firms' perspectives and analyzes company's action of including customers and how RCMD may influence firm’s performance. During the investigation it was found that RCMD comprises of different streams of literature that follow various conventions and remain very detached from one another. However, there are some common themes between these two streams of researches. For instance, customer knowledge and experience has all seems to be vital for RCMD from the two points of view, learning capacities of a customer and of a firm have both been discovered to be exceptionally important for RCMD. It was also found that significantly less exploration is done from the firm's viewpoint to understand what drives firms to receive RCMD and what prepares them to effectively preform it. Ultimately, there was absence of hypothetical improvement in all subareas. This article goes beyond existing researches by uniting various streams of studies, evaluating key differences related to the concept and findings on antecedents and outcomes of RCMD. This article suggest that future studies ought to embrace a consistent and predictable conceptualization of RCMD and restrain using wide terms.